(untitled) (Research, Society and Development, 2018)
This article is an integral part of the historical research that we do in the doctorate in education by the Federal University of Rio Grande do Norte, and aims to highlight the elements presented in the text, "Slójd and the moral education of the young", written by Aprígio Gonzaga, which was first published in the Journal of Education of Rio de Janeiro and republished in the Pedagogium Magazine (1925). This theme is recurrent in our historical research, for presenting evidence of the Escolanovista proposal, such as the need to re-elaborate education taking as a point of emphasis the implementation of manual work in educational practice, an element that will contribute to the moral formation of young people. In the text under analysis, the author supports the idea that the Slojd is basic to the constitution of the moral formation of learners, ie, that the insertion of manual labor as a formative aspect in human activity must be conceived as one of the pillars of formation moral. In order to reflect on the constitutive elements of the text, we used the work of Rosemary Dore Soares (2000), who, in discussing Gramsci’s proposal for education, elaborates a reflection on Slojd, a Swiss model of education that influenced American and Brazilian schools. In Rio Grande do Norte, we find traces of this proposal from the 1908s onwards. Another authored work is by Martha Aparecida Todeschini de Asuncion (2016), which analyzes the educational proposal of the author of the text, which, according to her, exerted a strong influence on the São Paulo teaching project aimed at training the worker. For that, we chose theoretical-methodological references of the new cultural history, that allow to use different sources and documents, associated to the new school, active school and educational practices.